Subsidized work before and after the German Hartz reforms: Design of major schemes, evaluation results and lessons learnt - Joachim Wolff; Gesine Stephan (IZA Journal of Labor Policy, 2013)
This review discusses empirical studies on hiring subsidies in the private sector and on schemes directly providing usually public or non-profit sector jobs for the unemployed in Germany. An important effect of hiring subsidies is that they stabilise employment. For employment schemes, results before the Hartz reforms imply mostly negative average treatment effects on regular employment outcomes of the treated, while results are mostly positive after introducing the reforms. During the years 2003 to 2005, the benefit system was radically reformed and now emphasizes mutual obligations. That might be one reason for changes in the effectiveness of job creation schemes.
Keywords: H53; J08; J68; 330; Hiring subsidies; Job creation schemes; Evaluation of active labour market programmes